Optimalisasi Perlindungan Konsumen dan Peningkatan Perdagangan Mata Uang Virtual di Indonesia: Studi tentang Peraturan Otoritas Jasa Keuangan - Ekawati, Dian; Tohir, Toto; Susanto, Susanto (Fakultas Hukum, Universitas Muslim Indonesia, 2023)
This study aims to normatively analyze OJK Regulation Number 3 of 2024, focusing on consumer protection in the context of the increasing trade in virtual currency in Indonesia. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that OJK Regulation Number 3 of 2024 is crucial in optimizing consumer protection and increasing virtual currency trading in Indonesia. Through the general provisions in OJK Regulation Number 3 of 2024, which cover consumer protection and the sandbox mechanism, the regulation supports responsible testing and development of FinTech innovations. The practical implementation of OJK Regulation Number 3 of 2024, emphasizing personal data protection and transparency, adds a layer of consumer protection. Overall, OJK Regulation Number 3 of 2024 creates an environment conducive to safe and regulated virtual currency trading, enhancing investor and consumer confidence in the Indonesian FinTech ecosystem. Therefore, it is recommended that the government and OJK, FinTech innovators and virtual currency traders, as well as consumers and investors, take strategic steps to enhance consumer protection and optimize virtual currency trading in Indonesia. The Government and OJK need to ensure the effective implementation of OJK Regulation Number 3 of 2024 through widespread socialization, strict supervision, and firm law enforcement against violations. FinTech innovators and virtual currency traders should develop robust risk management systems, enhance operational transparency, and ensure compliance with personal data protection provisions. Consumers and investors are advised to improve their digital financial literacy, critically assess investment risks, and interact only with platforms and service providers that have been verified and comply with OJK regulations. The collaboration between regulators, the industry, and the community will create a safer, more transparent, and sustainable virtual currency trading ecosystem, supporting the growth of the FinTech sector in Indonesia while minimizing potential risks for consumers and investors.